The Potential Aqueous Extracts of Medical Plant and Alum against Bacteria, an in Vitro Study - Shalah, Dr. Lubna Abdul Muttalib Al (International Journal of Psychosocial Rehabilitation, 2020)
Background: The attention for plants as well as to medicinal herbs has increased. It’s mainly as key sources for the foundation of medical drugs and a source of effective materials that go into the composition of the drug. Aim: In order to determine the medical significance of (Malvasylvestris, Matricariachmomilla, Salvia officinalis, Quercus infectoria, Curcuma Longa, and Alum)aqueous extract and its anti-microbial activity in contradiction of particular kinds within Gram positive, negative bacteria through incomes degree the distance of the inhibition zone against some types of Gram positive and negative bacteria by means measure the diameter of the inhibition zone (mm) Methods: These bacteria were randomly isolated from clinical samples of people whom Fallen asleep in Al-Hilla teaching hospital, Babylon during a period from October2016 to January 2017. In the present study; the diagnosis of bacterial strains where after its culturing proceeding within appropriate media (morphological feature) and then the diagnosis was performed by using conventional biochemical tests and Epi 20 system at the microbiological laboratory/College of Medicine/Babylon University. These strains were included; E.coli, Enterobacter, Klebsiella, Acinetobacter, proteus, Salmonella, and Pseudomonas. The results of this investigation have exposed that studied extract is effective in discouraging the development of these bacteria outside the body of the organism (Gram positive & Negative bacteria). CONCLUSION: from the above experiment, it was concluded that studied aqueous plant extracts has beneficial effect on tested pathogenic bacteria due to high concentration of energetic biochemical ingredient for antimicrobial action that useful for preventing certain enteric diseases.